Communicating citizenship in China’s digital society - Xiong, Bingjuan (2019)
This research explores the (inter-) cultural dimension of communicating citizenship in China’s new media environment. It adopts speech codes theory as a theoretical and methodological framework to examine the historically situated and socially constructed meanings of citizenship and the normative communicative conduct for practicing “good citizenship” in China. Through a systematic analysis of Chinese online discourse surrounding two social events, this study captures one speech code pertaining to communicating citizenship that is premised on a paradox–citizenship is interpreted by the Chinese as a legal entitlement that they deserve, but it is simultaneously treated as an aspirational and unattainable ideal. Additionally, speaking sensibly and morally with a communal orientation is heavily emphasized in this speech code as it is considered a valuable communicative practice for performing “good citizenship.” Finally, participating in online collective actions such as “topping posts” is rendered an acceptable and effective way to communicate and enact citizen rights in China.